A Technical Primer on Auction Theory I: Independent Private Values - Steven A. Matthews (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
This primer rigorously introduces the auction model of "risk neutral bidders with independent private values". The model is central to auction theory, and its structure is the same as a many models used in information economics. Results are derived regarding the nature of equilibria, the effects of entry fess and reserve prices, revenue equilivalence, and the design of optimal auctions. Widely applicable concepts are emphasized, such as revealed preference logic, the single-crossing property, and the Revelation Principle. Intended readers are economics graduate and advanced undergraduate students, and all economists who want to examine auction theory in detail.
Keywords: 330